Anarhistična politična misel in slovensko delavsko gibanje ob koncu 19. stoletja - Vodovnik, Žiga (Javnost (Ljubljana), 2010)
This article discusses the role of anarchism in the development of Slovene political thought and its legacy in the labour movement in Slovenia at the end of the nineteenth century. Slovene labour movement was able to overcome narrow nationalistic solutions and conceptions that both major political groupings in Slovenia of that time operated with. The article starts with the assumption that, similarly to other countries, important theoretical contributions in Slovenia were made by individuals who were involved, in one way or another, in a critical and reflective praxis of social movements. The article aims at contributing to the history of the anarchist political thought in Slovenia and, specifically, identifying epistemological, methodological and theoretical obstacles to its development.
Keywords: Slovenia; Slovenija; politična zgodovina; delavsko gibanje; anarchism; anarhizem